Didactic Effects in the Treatment of Animals in Chosen Robinsonades - Doms, Misia Sophia (Porównania, 2019)
Recently, the groundbreaking conference volume on Robinson’s animals (Robinsons Tiere, ed. Borgards, Klesse, Kling) has paid thorough attention to human-animal interaction in the Robinsonade genre. However, focussing on the ethical and political dimension of this species-transcending relationship, the contributions of this volume have paid but little attention to its didactical dimension, i.e. to the educational power, which the interaction with living or dead animals exerts on the respective Robinson character(s). The paper at hand offers a detailed study of these pedagogical effects, taking into account Defoe’s prototype as well as the Enlightenment-era German children’s book Robinson der Jüngere by Joachim Heinrich Campe, the monumental Swiss educational novel Der Schweizerische Robinson (known in Anglophone cultures as The Swiss Family Robinson) by Johann David and Johann Rudolf Wyss, the female Robinsonade Die Wand by the Austrian writer Marlen Haushofer and Life of Pi by the Canadian Yann Martel. In the texts from the 18th and 19th centuries, interacting with animals prepares the protagonists for a future leading position among their fellow men, while in the more recent Robinsonades by Haushofer and Martel the same process includes painful lessons, causing narcissistic wounds of one kind or another.